Learning English using children's stories in mobile devices. (17th March 2016) - Cavus, Nadire; Ibrahim, Dogan
Abstract: The topic of this paper is to describe the development of an interactive application that can be used in teaching English as a second language using children's stories in mobile devices. The aim of this experimental study has been to find out the potential of using the developed interactive mobile application in improving the learning skills such as vocabulary, pronunciation, listening and comprehension of the learners of the English language without the help of a teacher. The novelty of the research in this paper has been the use of a speech recognition engine on the mobile phone to identify spoken words of the learner in an attempt to teach correct pronunciation of words. The learning is interactive and it takes place entirely on a mobile phone. In this experimental study 37 voluntary students have participated. A Pre‐Test and a Post‐Test have been performed to find out the learning abilities of students. The results of the experimental study clearly indicated that English learning skills of young students had higher statistically significant improvements as a result of using the developed application in the experimental group. It can be concluded that the developed mobile application can be used as an educational tool in teaching English as a second language. Young students who may be interested in improving their listening, vocabulary, comprehension and pronunciation skills while learning English as a second language should find this mobile application enjoyable and useful.